Diversity and gradients of vegetation of Sivrihisar Mountains (Eskisehir-Turkey) - Balpinar, Neslihan; Kavgaci, Ali; Bingol, M. Umit; Ketenoglu, Osman (Acta Botanica Croatica, 2018)
This study was carried out to determine the plant communities and understand the main topographical driving factors of floristic differentiation in the Sivrihisar Mountains (Eskisehir Province). Vegetation samplings were carried out according to the Braun-Blanquet approach. The relevés were stored in the TURBOVEG database management program. Hierarchical classification was carried out in PC ORD program with Ward’s method and Euclidean distance as a resemblance measure. The diagnostic species were identified by a fidelity measure in the JUICE program. The results of the classification were visualized by ordination techniques in the CANOCO package by using principal component analysis. In conclusion, except for the degraded forest community, all the 7 steppe and 1 scrub plant communities studied were identified and described as new associations. Also, a syntaxonomical scheme for the vegetation of Sivrihisar Mountains was suggested.